An Integrated Curriculum in Malaysian Universities: A Conceptual Study - Hasnah, Haron; Mohd Ridzuan, Darun; Ishak, Ismail (ESB Business School, 2016)

(untitled)
In the year 1991, Malaysia has come out with the Vision 2020. Three main goals of this agenda are a high income economy, inclusiveness and sustainability. To assist in achieving these objectives, the Ministry of Higher Education has come out with The Malaysian Education Blueprint 2015-2025 (MEB) for Higher Education. This blue-print comes along the Eleventh Malaysia Plan. Both Plans chart the direction for Malaysia to achieve the Vision 2020. In 2015, higher education enrolment has increased by 70% to 1.2 million students over the last 10 years. The growth rate of research output and quality has been one of the highest in the world, and Malaysian institutions are ranked strongly among the Asian peers. Seeing this trend, Malaysia must adapt itself to the competitive global economic environment. This includes the transformation of Malaysia’s higher education system. The job scenario of tomorrow will require greater emphasis on science, technology, engineering and mathematics. The commercialization of ideas and industry research partnerships are expected to propel innovation. In addition to the above, a sustainable funding model with clear outcomes, incentives, and support for those who is need is most critical and crucial. Henceforth, this blueprint will transform Malaysia’s higher education system to meet these new challenges. Therefore, universities cannot anymore stand alone. So the curriculum put forth by Universities must be relevant and meeting the needs of the stakeholders. That is why the private sector will be encouraged to provide faculty and design curriculum that are tightly linked to required job skills, to co-fund research, and have off-take agreements for graduates. This is to ensure sustainability of universities in years to come. To make this happen universities cannot work in silo, they have to reciprocate by being innovative and relevant. It calls for curriculum at the universities to be integrated with various disciplines. This leads to the importance of combining technical and management skills. Graduates possessing both competencies are able to meet the demands of the work force in Malaysia. There is also a need to focus on green growth and sustainable development issues where universities become the agent of change that promote development which is ecologically, socially and economically sustainable. The paper discusses two multi-disciplinary programs that focus both on sustainable development and business engineering. Of late, these two sectors have grown in importance internationally and in the local arena. In all cases, the change in the education agenda has been brought about by the movement that believes that a change has to be made. Industrial players, the government and professionals have been seen to play an important role in realising this agenda. For example, although business engineering is technical in nature but courses in the areas of soft skills and human values such as ethics, risk and governance are also offered in addition to engineering courses. By nature they complement the hard skills and in a long run will ensure the sustainability of the projects and also to preserve sustainability of economy while at the same time preserving the environment and society.